Hydrogen bonding-induced high-performance stretchable organic semiconductors: a Review - Chen, Jinhan; Wang, Zheng; Deng, Zhifeng; Chen, Ligui; Wu, Xuhui; Gao, Yihan; Hu, Yumeng; Li, Mei; Wang, Hongzhen (Frontiers in Chemistry, 2023)
Semiconductors are widely used in electron devices. With the development of wearable soft-electron devices, conventional inorganic semiconductors are unable to meet the demand because of their high rigidity and high cost. Thus, scientists constructed organic semiconductors with high charge mobility, low cost, eco-friendly, stretchable, and so on. Due to the excellent performance of stretchable organic semiconductors, they can be widely used as wearable soft-electron devices, such as stretchable Organic field-effect transistors (OFETs), Organic solar cells (OSCs), and so on. Contains flexible display devices and flexible power sources, which are of great interest for applications of future electron devices. However, there are still some challenges that need to be solved. Commonly, enhancing the stretchability may cause the degradation of charge mobility, because of the destruction of the conjugated system. Currently, scientists found that hydrogen bonding can enhance the stretchability of organic semiconductors with high charge mobility. Thus in this review, based on the structure and design strategies of hydrogen bonding, various hydrogen bonding induced stretchable organic semiconductors are introduced. In addition, the applications of the hydrogen bonding induced stretchable organic semiconductors are reviewed. Finally, the stretchable organic semiconductors design concept and potential evolution trends are discussed. The final goal is to outline a theoretical scaffold for the design of high-performance wearable soft-electron devices, which can also further advance the development of stretchable organic semiconductors for applications.